THE APPLICATION OF THE ROBSON METHOD TO ANALYSIS AND SEARCH FOR OPPORTUNITIES TO REDUCE THE FREQUENCY OF CAESAREAN SECTIONS IN THE REPUBLIC OF KHAKASIA - Валентина Сергеевна Гладкая; Ольга Александровна Любчич; Александр Владимирович Тышта; Дарья Дмитриевна Рощина (The Publishing House Medicine and Enlightenment, 2023)
Purpose - to analyze the frequency of caesarean sections using the method of M. Robson, to assess the possibility of reducing this indicator in the Republic of Khakassia. Material and methods. It was carried the retrospective and comparative analysis out of according to the 10-group classification of M. Robson by a continuous method: 2226 birth histories that took place over 8 months from January to August 2022 and 3606 birth histories for 2020 in the Republican Clinical Perinatal Center, Abakan. Results. In 2022, compared to 2020, there was an increase in the frequency of caesarean sections in the RCPC due to groups 1, 5, 6, 7, 8, while there is a decrease in groups 2, 3, 4. Careful selection of patients for induction of labor made it possible, on the one hand, to increase the frequency of delivery through the natural birth canal in induced labor (groups 2, 3, 4). There is the increase in operative delivery in groups with spontaneous development of labor (group 1), vaginal delivery with the scar on the uterus (group 5), breech presentation of the fetus (group 6 and 7) and multiple pregnancy (group 7). Conclusions. The Robson classification allows to analyze the frequency of caesarean sections in dynamics and find ways to reduce it in an obstetric hospital of the 3rd level. The greatest influence on the overall incidence of CS in the Perinatal Center is exerted by the proportion of abdominal delivery in groups of singleton full-term pregnancies in cephalic presentation, including those with a history of caesarean section (groups 1 and 5) and births in breech presentation (groups 6 and 7).